The Influence of Age Advancement and of Comorbidities on the Functional Capacity of Patients After the Incident of Ischemic Stroke - Beata Haor; Mariola Głowacka; Agnieszka Kalinowska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The occurrence of ischemic strokes, particularly with people over 65 years of age, results from the presence of comorbidities that may adversely affect both the early and late prognosis as well as functional capacities of patients. Aim. The aim of the study was to evaluate the efficiency regarding basic daily activities performed by patients after the incident of the ischemic stroke, depending on the advancement of their age and the on the presence of comorbidities. Material and Methods. The study was carried out among 65 patients hospitalised due to the ischemic stroke in the neurology ward of the Provincial Hospital in Plock. The analysis of the functional capacity of patients, with the use of the Barthel Scale Questionnaire, was performed twice: on the first day of their hospitalisation and on the day of discharge from the hospital ward. Results. The functional capacity of the patients within the period of hospitalization after the incident of ischemic stroke was improving as a result of treatment, rehabilitation and care. However, both on the day of admission to the ward, as well as at discharge, the patients aged over 65 had the lowest scores on the Barthel Scale Questionnaire. The presence of comorbidities, particularly among older respondents, contributed to the deterioration of patients’ functional capacity. Conclusions. 1). Patients after the incident of ischemic stroke, despite the improvement regarding their functional capacity, require assistance in the performance of daily activities. 2). Age advancement contributes to the reduction of the functional capacity of respondents after the incident of ischemic stroke. 3). Comorbidities of the incident of ischemic stroke as well as the prior episode of stroke significantly contribute to the decrease the functional capacity of respondents. (JNNN 2015;4(3):102–108)